Broad Brush Surveys: a rapid qualitative assessment approach for water and sanitation infrastructure in urban sub-Saharan cities - Nel, Melissa; Simuyaba, Melvin; Muchelenje, Justina; Chirwa, Taonga; Simwinga, Musonda; Speight, Vanessa; Mhlanga, Zenzile; Jacobs, Heinz; Nel, Nicole; Seeley, Janet; Mwanaumo, Erastus; Viljoen, Lario; et al. (Frontiers in Sustainable Cities, 2023)
Broad Brush Surveys (BBS) are a rapid, qualitative assessment approach using four meta-indicatorsphysical features, social organisation, social networks and community narratives -to gauge how local context interfaces with service/intervention options, implementation and uptake. In 2021, responding to rapid urbanization and the accompanying need for water and sanitation services, BBS was innovatively applied by social scientists and engineers to assess water and sanitation infrastructure, both formal and informal, in two African cities -Lusaka and Cape Town. In four urban communities, identified with local stakeholders, BBS data collection included: four mapping group discussions with local stakeholders (participants = 24); eight transect walks/drives; 60 structured observations of water and sanitation options, transport depots, health facilities, weekends, nights, rainy days; seven mixed gender focus group discussions (FGDs) with older and young residents (participants = 86); 21 key-informant interviews (KII, participants = 21). Findings were rapidly summarized into community profiles, including narrative reports, maps and posters, and first discussed with community stakeholders, then at national/provincial levels. The metaindicator framework and set sequence of qualitative activities allowed the detail on water and sanitation to gradually emerge. For example, the mapping discussion identified water sources considered a risk for waterborne infections, further observed in the transect walks and then structured observations, which compared their relative condition and social interactions and what local residents narrated about them. FGDs and KIIs elaborated on the control of these sources, with nuanced detail, including hidden sources and the use of different water sources for different activities also emerging. We demonstrated that despite some limitations, BBS provided useful insight to systems and social processes surrounding formal and informal water and sanitation infrastructure in and across designated urban areas. Furthermore, BBS had the potential to galvanise local action to improve infrastructure, and illuminated the value of informal options in service delivery.